SINTESIS SENYAWA 1,4-BIS [(2-HIDROKSI-3-METOKSI-5- FORMALDEHID-FENIL)-METIL] PIPERAZIN DARI BAHAN DASAR VANILIN DAN UJI AKTIVITASNYA SEBAGAI ZAT ANTIOKSIDAN - Susy Yunita Prabawati; Andika Fajar Setiawan; Arini Fawzia Agustina (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2012)
A study has been conducted to synthesize 1,4-bis [(2-hydroxy-3-methoxy-5-methanal- phenyl)-methyl] piperazin using vanillin as a starting material. It was of interest to investigate the activity of that compound, as an antioxidant with DPPH method. The synthesis was carried out through Mannich reaction using vanillin, formaldehida, and piperazin. The product was obtained as a white solid, melting point 245-2470C with a yield of 67.49%.Characterization of the product by IR and 1H NMR spectrophotometry, showed the formation of methylene bridge. This indicated that the compounds synthesized was 1,4-bis [(2-hydroxy-3-methoxy-5-methanal-phenyl)-methyl] piperazin. The test of antioxidant activity with DPPH method showed that 1,4-bis [(2-hydroxy-3-methoxy-5-methanal- phenyl)-methyl] piperazin had antioxidant activity better than vanillin with IC50 values was 0.661 mM while vanillin was 3.158 mM.